2004
DOI: 10.1074/jbc.m400895200
|View full text |Cite
|
Sign up to set email alerts
|

Translationally Controlled Tumor Protein Interacts with the Third Cytoplasmic Domain of Na,K-ATPase α Subunit and Inhibits the Pump Activity in HeLa Cells

Abstract: Translationally controlled tumor protein (TCTP) is a growth-related protein under transcriptional as well as translational control. We screened a rat skeletal muscle cDNA library using yeast two-hybrid system and found that TCTP interacts with the third large cytoplasmic domain of ␣1 as well as ␣2 isoforms of Na,K-ATPase, believed involved in the regulation of Na,K-ATPase activity. Interaction between TCTP and Na,K-ATPase was confirmed by coimmunoprecipitation in yeast and mammalian cells. We also showed, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 33 publications
3
75
0
1
Order By: Relevance
“…They reported that overexpression of TCTP in HeLa cells resulted in tyrosine phosphorylation of the epidermal growth factor receptor and in activation of both the Ras/Raf/ ERK and the PI3K/Akt pathways (Kim et al 2009b). In a more recent paper, they provided a link to the activity of TCTP in binding to and inhibiting the Na,KATPase, which they had observed earlier (Jung et al 2004). The authors found that TCTP in binding to the third cytoplasmic domain of the Na,K-ATPase results in release and activation of the protein kinase Src and consequently in the activation of the PI3K/Akt and the Ras/Raf/ERK pathways, as well as of additional signalling pathways .…”
Section: Tctp and Cell Growth Regulationmentioning
confidence: 83%
See 2 more Smart Citations
“…They reported that overexpression of TCTP in HeLa cells resulted in tyrosine phosphorylation of the epidermal growth factor receptor and in activation of both the Ras/Raf/ ERK and the PI3K/Akt pathways (Kim et al 2009b). In a more recent paper, they provided a link to the activity of TCTP in binding to and inhibiting the Na,KATPase, which they had observed earlier (Jung et al 2004). The authors found that TCTP in binding to the third cytoplasmic domain of the Na,K-ATPase results in release and activation of the protein kinase Src and consequently in the activation of the PI3K/Akt and the Ras/Raf/ERK pathways, as well as of additional signalling pathways .…”
Section: Tctp and Cell Growth Regulationmentioning
confidence: 83%
“…Na-K-ATPase C-terminus Na-K-ATPase inhibition Jung et al (2004), Kim et al (2008a) Sorting nexin 6 (SNX6) Na-K-ATPase activation Yoon et al (2006) Ca 2+ N-and C-terminus Ca 2+ -scavenging Feng et al (2007a), Graidist et al (2007), Kim et al (2000) Vitamin-D3 1. Cooperation with other anti-apoptotic proteins.…”
Section: Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that translationally controlled tumor protein (TCTP) binding to the cytoplasmic domain of Na, K-ATPase a subunit results in the activation of EGFR and its downstream signaling pathways related to cell survival and motility (Jung et al, 2004;Kim et al, 2009). Thus, it appears that Na,K-ATPase inhibition by TCTP induces Src activation.…”
Section: Introductionmentioning
confidence: 99%
“…Several additional molecular interactions and regulatory functions have been reported for TCTP: (1) the protein binds to the Na þ , K þ -ATPase and inhibits this enzyme (Jung et al, 2004). This observation is consistent with the demonstration that TCTP overexpression in mice results in systemic hypertension (Kim et al, 2008b); (2) TCTP interacts with protein synthesis elongation factor eEF1A and negatively regulates the guanosine-nucleotide-exchange reaction on eEF1A (Cans et al, 2003); (3) a study using gene knockdown in Drosophila reported the activity of TCTP as a guanine-nucleotide-exchange factor for the small GTPase, Rheb, and indicated involvement of TCTP in the target of rapamycin (TOR) signalling pathway (Hsu et al, 2007); however, recent results from our own (Wang et al, 2008) and two other laboratories (Chen et al, 2007;Rehmann et al, 2008) are not compatible with this conclusion.…”
Section: Introductionmentioning
confidence: 99%